2020
DOI: 10.1016/j.coelec.2019.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Current atomic-level understanding of electrochemical nucleation and growth on low-energy surfaces

Abstract: This review presents recent progress in the understanding of electrochemical phase formation on low-energy substrates, which is essential for metal electrodeposition and the design of stable batteries. Advanced characterization techniques and ultrasensitive electrochemical instrumentation give access to experimental data that were not available a few years back. Besides, the continuous development of theoretical models gradually provides a more complete description of multiple nucleation. However, important co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 67 publications
0
43
0
Order By: Relevance
“…The focus is set on correlating innovative electrochemical growth strategies with the field of application and mechanistic understanding of the electrodeposition process. This paper complements our recent review of the latest advances in electrochemical nucleation and growth [8].…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The focus is set on correlating innovative electrochemical growth strategies with the field of application and mechanistic understanding of the electrodeposition process. This paper complements our recent review of the latest advances in electrochemical nucleation and growth [8].…”
Section: Introductionmentioning
confidence: 56%
“…In general, we expect that electrodeposition will keep unravelling its potential as the preferred method for electrocatalyst synthesis, once a deeper understanding of the electrochemical growth process [8] is attained for complex chemistries and surfaces. This would allow 1) better controlling the morphology and the surface composition of complex bifunctional electrocatalysts, and 2) studying, in a systematic way, the interplay of kinetics and mass transport during electrocatalysis at nanostructured electrodes.…”
Section: Analysis Of Innovative Electrodeposition Strategies and Conclusionmentioning
confidence: 99%
“…Complementary high‐resolution STEM imaging revealed that a range of nanostructures from single Pt atoms (imaged directly on the CCTG support) to amorphous, monocrystalline, and polycrystalline PtNPs (and aggregates of these) coexist during the early stages of nucleation and growth, providing further support to the recently proposed electrochemical aggregative growth mechanism. [ 42 ]…”
Section: Local Ensemble Measurementsmentioning
confidence: 99%
“…The electrodeposition of metal-based nanostructures is paramount in various applications (next-generation transistors, or preparation of active electrodes). [1,2] This is because the control of the electrode current or potential enables to predict the nature of the electrodeposits (composition, size, etc.). However, such prediction is more complex for earthabundant iron group elements whose electrochemical reduction competes with inhibiting reactions such as water reduction.…”
mentioning
confidence: 99%
“…[12] To apprehend the contributions of such competing chemical pathways, a complementary in situ signature is needed. [2,[13][14][15][16][17] E.g. coupling electrochemistry to high resolution label-free optical microscopy [15][16][17] has proved to be effective to monitor metal deposition at single NPs with high temporal resolution and sensitivity, [18][19][20][21] as well as to differentiate metallic NPs from other nanoobjects (e.g.…”
mentioning
confidence: 99%